Developing audio data hiding scheme using random sample bits with logical operators - Mohammed Hatem Ali Al-Hooti; Tohari Ahmad; Supeno Djanali (Institute of Advanced Engineering and Science, 2019)
Sharp development progress of information technology has affected many aspects including data security. This is because classified data are often transferred between systems. In this case, data hiding exists to protect such data. Some methods which have been proposed, however, are not yet optimal concerning the amount of the secret and the quality of the resulted stego data. In this paper, we explore an audio file as the medium to carry the secret data which has been extracted into binary. Before the process begins, the cover is converted to binary and each sample’s bits are divided into two groups, one is used as the location of the embedded 4 bits whereas the second part locates the two bits that are randomly selected as the key. The experimental results have validated that the capacity is high and there is no much impact on the quality. Moreover, compared to the current LSB methods the security is exceedingly enhanced.